A systematic review involving 11, 187 participants evaluating the impact of COVID-19 on anxiety and depression in pregnant women. (3rd April 2021) - Sun, Fengli; Zhu, Jianfeng; Tao, Hejian; Ma, Yongchun; Jin, Weidong
Abstract: Background: COVID-19 has started to spread within China since the end of December 2019. As a special population, the pregnant and delivery women maybe influenced both in physical and psychological aspects. The meta-analysis was conducted about mental health in pregnant and delivery women. Methods: We searched both MEDLINE, EMBASE, Cochrane Library in English and CBM, CNKI, WANFANG and CSSCI in Chinese to find literature from December 2019 to 31 July 2020 related to COVID-19 and mental health in patient with pregnancy and delivery, among which results such as comments, letters, reviews and case reports were excluded. The prevalence of anxiety and depression in the population was synthesized and discussed. Results: A total of 11, 187 subjects were included in 15 studies. Random effect model is used to account for the data by Revman 5.2. The results showed that the prevalence of depression was 30% (95% CI: 0.23–0.37), the prevalence of anxiety was 34% (95% CI: 0.26–0.43) and prevalence of both anxiety and depression was 18% (95% CI: 0.09–0.29). The prevalence of anxiety (OR = 2.15, 95% CI: 1.39–3.31, Z  = 3.47, p =.0005), depression (OR = 1.95, 95% CI: 1.07–3.56, Z  = 2.19, p =.03) were higher than that of controls. Significant heterogeneity was detected across studies regarding these prevalence estimates. Subgroup analysis was taken according to assessment tools, and sensitivity analysis was done to explore the sources of heterogeneity. Conclusions: The higher prevalence of depression, anxiety, both depression and anxiety in women with pregnancy and delivery during COVID-19 pandemic although the significant heterogeneity detected in studies. We must interpret the results with caution and also put attention to this result. As the epidemic is ongoing, it is vital to set up a comprehensive crisis prevention system.